The effect of lean on occupational health and safety and productivity in the garment industry – a literature review. Issue 1 (1st January 2019) - Hamja, Abu; Maalouf, Malek; Hasle, Peter
ABSTRACT: Introduction : Lean is increasingly used by garment manufacturers to increase productivity for reducing costs and lead time. Yet, it has not been documented in a review whether lean actually improves productivity, and it is an open question whether lean can improve productivity without jeopardizing occupational health and safety (OHS). Objective : This article contributes to this debate by reviewing the present knowledge about the effect of lean on productivity and OHS in the RMG industry. Methodology : A systematic review of the available peer-reviewed studies of lean in RMG and its related effects on productivity and OHS. Results : We identified 18 relevant articles, which showed strong positive effect of lean on productivity and weak positive to mixed effects of lean on OHS. Conclusions : Our results indicate that lean in RMG is likely to improve productivity, but RMG manufacturers need to make careful assessment of the effect of lean on OHS and adjust lean implementation accordingly.